Analysis of Illegal Investment in the Perspektive of Pancasila : Analisis Hukum Investasi Bodong dalam Perspektif Pancasila - Arie Ramadhani; Desi Yunita Putri; Roudhotul Jannah (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2023)
This study aims to find out the contract or investment cooperation agreement made by partners and PT. IMB is legally valid, to find out the agreement between PT. MIB with partners is an investment agreement, to find out the business run by PT. MIB with partners is an illegal investment to know PT. IMB commits fraud under the guise of investing in victims as partners, to find out about illegal investment laws from the perspective of Pancasila. In this study, researchers used field research methods and used a qualitative approach. The results of the research found that the cooperation agreement entered into by partners and PT.IMB was not legally valid. The agreement between PT.MIB and partners is an investment agreement but there are some irregularities, PT. IMB commits fraud under the guise of investment. Conclusion The agreement between PT. MIB and partners is an investment agreement even though there are some irregularities, but PT. MIB is not competent at law because it does not have permission to accept investment from investors, both domestic and foreign. If seen from the characteristics of fraudulent investment, PT. MIB is running an illegal investment business.